FUNGSI BHP SEBAGAI WALI PENGAWAS TERHADAP ANAK DI BAWAH PERWALIAN DALAM RANGKA PERLINDUNGAN ANAK (STUDI KASUS DI BHP SEMARANG) - Heriyani, Endang; Yuniarlin, Prihati (Jurnal Media Hukum, 2015)
According to Article 45 paragraph (1) Regulations No 1 1974 about marriage, both of the parents have obligation to take care and educate their children as well as possible. But in fact, many events can be watched on parents who do not do their duties as parents. Children who are not in the authority of their parents, will be placed under the guardianship. According to Article 306 of the book of the civil law act in guardianship there should be a guardian which is run by the Heritage Hall. The problem rises is the existence of the Heritage Hall as the guardian watch in guardianship that can give protection to the children under the guardianship and how are the efforts to optimize the function of the Heritage Hall as the guardian watch to the children under the guardianship. This research is a normative and an empirical law research. The conclusion of this research is that the guardian's obligations and the obligations of the Heritage Hall as the guardian watch if it is executed to provide protection to the children, both the personality and the treasure. Thus, the position of Heritage Hall as the guardian watch needs to be maintained. The efforts of Heritage Hall to optimize the function of the Heritage Hall as the guardian watch can be reached by the bill of draft legislation about Heritage Hall. By maintaining the provisions of the book of civil law act or S 1872 No 166 on the instruction of Heritage Hall, which are still needed by the Heritage Hall in doing the duties.